Letter from Ungku to Datin P Lim Pui Huen - Ungku Abdul Aziz, Ungku Abdul Hamid
This is a reply letter from Ungku to Datin P Lim Pui Huen. Ungku has promised to write a review for Dr. Othman Mohd Yatim's Batu Acheh: Early Islamic Gravestones in Peninsula Malaysia.